PENERAPAN PENDEKATAN STEM ( SCIENCE, TECHNOLOGI, ENGINEREENG AND MATHEMATICS ) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Indriyani, Amalia; Jalal, Muhaiminah; Saputri , Vioni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research was conducted in response to learning conditions in IPAS that indicated students’ creative thinking skills had not yet developed optimally. The study aimed to describe the impleme ntation of the STEM (Science, Technology, Engineering, and Mathematics) approach in enhancing students’ creative thinking skills in IPAS learning, to identify challenges encountered during the application of STEM-based instruction, and to explain the efforts undertaken to address these challenges among fourth-grade students of MI Raudhatul Muhajirin. The research employed a Classroom Action Research design implemented in two cycles, each consisting of four stages: planning, action, observation, and reflection. Data were collected through observation, interviews, documentation, and questionnaires, with fourth-grade students of MI Raudhatul Muhajirin as the research subjects. The findings revealed a significant improvement in students’ creative thinking skills following the implementation of the STEM approach, increasing from 31% in the pre-cycle to 69% in Cycle I and reaching 93% in Cycle II, categorized as very good. In addition, teacher and student activity levels improved from 70% in Cycle I to 90% in Cycle II. These results indicate that the STEM approach is effective in enhancing students’ creative thinking skills in IPAS learning, particularly on the topic of kinetic energy for fourth-grade students at Madrasah Ibtidaiyah Raudhatul Muhajirin Muaro Jambi